2022
DOI: 10.3389/fimmu.2022.955390
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Analysis Reveals Macrophage–Tumor Crosstalk in Hepatocellular Carcinoma

Abstract: As one of the most malignant cancer, hepatocellular carcinoma (HCC) has a complex ecosystem featured by high heterogeneity. Cell crosstalk is demonstrated to be critical for HCC development. However, the cell communication orchestration in HCC remains largely unknown. Here, by analyzing the single-cell transcriptomes of the primary tumor tissues (n = 10) and tumor-adjacent tissues (n = 8) derived from 10 patients with HCC, we found that the proportions of plasmacytoid dendritic cells (pDCs) and natural killer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(42 reference statements)
2
11
0
Order By: Relevance
“…Furthermore, these enhanced communications activated downstream target genes that were involved in cancer-related pathways, including the TGF-beta signaling pathway, MAPK signaling pathway, EMT-related pathways, and integrin cell surface interactions, leading to tumor progression and poor clinical GC outcomes. Liu et al showed that the SPP1-CD44 axis in hepatocellular carcinoma (HCC) leads to tumor progression, and that this axis could not be identified in the tumor-adjacent tissues of HCC, which is similar to the findings of our present study [45]. Recently, an in vitro study confirmed our findings regarding the role of the SPP1-CD44 axis in the tumorigenesis function of prostate cancer and found downstream pathways to promote tumor progression [46].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, these enhanced communications activated downstream target genes that were involved in cancer-related pathways, including the TGF-beta signaling pathway, MAPK signaling pathway, EMT-related pathways, and integrin cell surface interactions, leading to tumor progression and poor clinical GC outcomes. Liu et al showed that the SPP1-CD44 axis in hepatocellular carcinoma (HCC) leads to tumor progression, and that this axis could not be identified in the tumor-adjacent tissues of HCC, which is similar to the findings of our present study [45]. Recently, an in vitro study confirmed our findings regarding the role of the SPP1-CD44 axis in the tumorigenesis function of prostate cancer and found downstream pathways to promote tumor progression [46].…”
Section: Discussionsupporting
confidence: 91%
“…Recent research has revealed malignant cells may act as a bridge between HCC malignant cells and macrophages, promoting macrophage transformation, in which SPP1-CD44 plays an important role. Similar results were found in pancreatic cancer and lung squamous cell carcinoma [32][33][34], and may also be suitable for colorectal cancer.…”
Section: Spp1 Plays An Important Role In Cellular Communication In Co...supporting
confidence: 81%
“…Immune infiltrating cells in the tumor microenvironment (TME) have been shown to play a key role in tumor progression and influence clinical outcomes in cancer patients. Single-cell RNA sequencing (scRNA-seq) identified that SPP1-CD44 axis was a unique interaction between macrophages and HCC malignant cells, suggesting the role of macrophage-derived SPP1 in the progress of HCC [ 40 ]. Another single-cell and spatial analysis revealed interaction of FAP + fibroblasts and SPP1 + macrophages in colorectal cancer, and their presence is negatively correlated with lymphocyte infiltration and predicted a poor patient survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%